2007
DOI: 10.1016/j.vetpar.2006.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate profiling and protein identification of tegumental and excreted/secreted glycoproteins of adult Schistosoma bovis worms

Abstract: Schistosoma bovis is a parasite of wild and domestic ruminants that is broadly distributed throughout many tropical and temperate regions of the old world. S. bovis causes severe health problems and significant economic losses in livestock, but in contrast to human schistosomes, S. bovis has been little investigated at a molecular level. Since schistosome glycans and glycoproteins can play important roles in the host-parasite interplay, the aims of the present work were: (i) to characterize the glycans express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents.…”
supporting
confidence: 70%
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents.…”
supporting
confidence: 70%
“…After N‐glycosidase digestion and subsequent Western immunoblotting of the ESP in the MW range 70–75 kDa, the enolase was detected at the expected MW. The glycosylation of enolases has been previously reported in other trematodes such as S. bovis (28). In our case the glycosylation of this isoform of E. caproni enolase appears to affect the target epitopes recognized by the antirecombinant enolase antibodies.…”
Section: Discussionmentioning
confidence: 56%
“…Our group has obtained preliminary data about the glycosylation state of specific proteins like enolase (Sotillo et al 2008) . The combination of 1DE or 2DE with lectin-binding and mass spectrometry could help to identify and characterize most of the echinostome proteins capable of binding lectins, similar to that already described for Schistosoma bovis (Ramajo-Hernández et al 2007a) .…”
Section: Advances In Echinostome Proteomicsmentioning
confidence: 78%